The influence of moisture on the in vitro embryo germination and morphogenesis of babassu (Orbignya phalerata Mart.) - doi: 10.4025/actasciagron.v34i4.13429 (Acta Scientiarum. Agronomy, 2012)
The objective of this study was to evaluate the physiological quality of babassu (Orbignya phalerata Mart.) embryos as a function of desiccation. The fruits were placed in a convection oven at 37±2°C for 0, 3, 6, 9, or 12 days. After these periods, the moisture contents of the fruits and seeds were determined. A reduction in the water content occurred more rapidly in the fruits than in the seeds. The decrease in seed moisture content from 12.59% (on the basis of fresh weight) to 4.56% did not affect the percentage of germinated zygotic embryos; however, we did observe a decline in the vigor as the seed moisture content decreased. Embryos with a 4.56% moisture content developed into seedlings of shorter lengths after 30, 60, and 90 days of in vitro growth. The longest seedlings originated from embryos with a 10.42% moisture content after 90 days. Thus, it was evident that the babassu embryos were tolerant to desiccation, whereas the seedling length was negatively affected by a reduction in the seed moisture content. Therefore, babassu fruits may be dehydrated and stored without losing their viability, which thereby guarantees the conservation of their germplasm.